163k views
5 votes
Show the steps to get full credit
3 (2x + 2) = 18 + 4(x - 5)

User AshleyS
by
5.8k points

2 Answers

4 votes

Answer:

x = -4

Explanation:

3(2x + 2)=18 + 4(x - 5)

6x + 6= 18 +4x - 20

6x - 4x = -2-6

2x = -8

x = -4

User Nirmal Raj
by
5.5k points
2 votes

Answer:


x=-4

Explanation:

So we have the equation:


3(2x+2)=18+4(x-5)

Distribute the left and the right:


3(2x)+3(2)=18+4(x)+4(-5)

Simplify:


6x+6=18+4x-20

Combine on the right:


6x+6=4x-2

Subtract 4x from both sides. The right cancels:


(6x+6)-4x=(4x-2)-4x\\2x+6=-2

Subtract 6 from both sides. The left cancels:


(2x+6)-6=(-2)-6\\2x=-8

Divide both sides by 2:


(2x)/2=(-8)/2\\x=-4

Thus, the value of x is -4.

User Apcelent
by
5.0k points